STUDI KASUS PESERTA DIDIK YANG MEMILIKI PRESTASI BELAJAR RENDAH KELAS XI MAN 2 PONTIANAK - Putri Khairunnisa; Yuline Yuline; Luhur Wicakso (Universitas Tanjungpura, 2018)
AbstractThis study aims to reveal about the relief efforts that will be given to learners in MAN 2 Pontianak who have low learning achievement. The method used is descriptive in the form of survey. The conclusion of this research is that based on the results of research conducted on case I subjects, it is found that the internal factors that affect the subjects of case I are: lack of motivation, lack of interest in the subjects of SKI and the lazy nature of learning owned by case I subjects, : time spent subjects case if coming home from school and finished tutoring is playing HP and going out to play with friends. Furthermore, in case II, it is found that internal factors affecting case II subjects are: case II subjects including children who studied diligently but lack of academic ability especially in jurisprudence subject cause case subjects always get low score on the subject, besides case subjects also lacked interest in fikh subjects. The counseling model used to help case I subjects is a model of REBT counseling with a shame attack technique. While case II subjects use REBT counseling model with behavior dispute technique.Keywords : Case Study, Learners, Low Learnig Achievement